PERLINDUNGAN PEREMPUAN LANJUT USIA KORBAN BENCANA GEMPA BUMI MELALUI TRADISI SUMBAYANG 40 DI SUMATERA BARAT - Silfia Hanani (Kafa`ah: Journal of Gender Studies, 2016)
Indonesia is one of disaster-prone countries. The disasters in Indonesia have destructed infra and supra structure that evoked more problems in human life, in example, the problems faced by elderly women. Not feasible residence, poor health service, and not guaranteed well-being are the examples of negative effect of disaster for elderly women. Therefore, elderly women face a dilemmatic situation that disrupts their life. Related to this poor condition post of earthquake in 2009, some tarekhat ulamas in West Sumatera performed a protection act through sumbayang 40 (40 praying). By means of this religious tradition, the elderly women who were disrupted by the earthquake gain protections from this activity such as religious education, economic support, psychological recovery, and settlement protection. As the result, the elderly women who followed this tradition obtained a well-being guarantee in the post disaster phase. Consequently, direct or indirect, sumbayang 40 tradition that is established in Minangkabau, contributes in achieving the goal of Millennium Development Goals (MGDs) program and improving life quality of elderly women.